2010
DOI: 10.1111/j.1523-5378.2010.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term Therapy with Celecoxib and Lansoprazole Modulates Th1/ Th2 Immune Response in Human Gastric Mucosa

Abstract: Celecoxib and lansoprazole modulate Th1/Th2 immune response in human gastric mucosa. The use of these drugs may interfere with long-term course of gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…It has been previously demonstrated that prostaglandins stimulate the production of IL-6 by bone cells 33 . This hypothesis is in agreement with the observation that OA patients treated with celecoxib exhibit decreased IL production in the gastric mucosa 34 . Therefore, the effect of NSAIDs on the IL-6 concentration is unlikely to be tissue specific.…”
Section: Discussionsupporting
confidence: 93%
“…It has been previously demonstrated that prostaglandins stimulate the production of IL-6 by bone cells 33 . This hypothesis is in agreement with the observation that OA patients treated with celecoxib exhibit decreased IL production in the gastric mucosa 34 . Therefore, the effect of NSAIDs on the IL-6 concentration is unlikely to be tissue specific.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, other studies even proposed an association between the intake of PPIs and decreased tumorigenesis, which in some of these studies was beyond the mucosa healing e ect of the drugs [61,62]. Further more, lansoprazole treatment was described to down-regulate 1 and 2 signaling pathways in the human gastric mucosa [63] and to be associated with decreased levels of proin ammatory cytokines such as interleukin(IL-)6, IL-8 and tumor necrosis factor-(TNF-)α in cultured tracheal epithelial cells [64]. Interestingly, PPIs were also reported to inhibit IL-4 and IL-13 signaling via STAT6 (signal transducer and activator of transcription 6) [65] and in PPI-REE a marked reduction of eotaxin-3, IL-13, IL-5 mRNA expression was observed a er PPI treatment [66].…”
Section: Acid Suppression Medication and The Immune Responsementioning
confidence: 79%
“…Third, the host immune response to high‐dose proton‐pump inhibitors (PPIs) in HP eradication regimens must be considered. PPIs may directly affect the immune response via the inhibition of gastric acid production . It has been shown that exposure to acid enhances the expression of adhesion molecules and cytokines, such as IL‐8 and IL‐1β, which in turn increases the inflammation and thus possibly recruiting immune cells .…”
Section: Discussionmentioning
confidence: 99%
“…PPIs may directly affect the immune response via the inhibition of gastric acid production. [55][56][57][58] It has been shown that exposure to acid enhances the expression of adhesion molecules and cytokines, such as IL-8 and IL-1β, which in turn increases the inflammation and thus possibly recruiting immune cells. 59,60 Therefore, acid reduction via PPIs may reduce these responses and also minimize food allergen simulation caused by acid-induced damage to the gastric mucosa.…”
Section: Discussionmentioning
confidence: 99%